Frontispiece: Traceless Removal of Two Kernel Atoms in a Gold Nanocluster and Its Impact on Photoluminescence. Issue 16 (1st April 2021) - Zhou, Yue; Liao, Lingwen; Zhuang, Shengli; Zhao, Yan; Gan, Zibao; Gu, Wanmiao; Li, Jin; Deng, Haiteng; Xia, Nan; Wu, Zhikun
Abstract : Nanoclusters The synthesis and characterization of two novel gold nanoclusters is reported by Nan Xia, Zhikun Wu et al. in their Communication on page 8668 . The traceless removal of two kernel atoms has been achieved for the first time.